Effectiveness of 14-day high-dose dual therapy for Helicobacter pylori infection in Vietnam - Phan, Nam T; Truong, Long H (The Journal of Infection in Developing Countries, 2025)
Introduction: The eradication rates of Helicobacter pylori (H. pylori) in Vietnam, with both triple therapy and non-bismuth quadruple therapy, have significantly declined due to increasing antibiotic resistance. This prospective study aimed to evaluate the eradication efficacy of high-dose dual therapy (HDDT) with esomeprazole and amoxicillin in a region with high resistance rates to clarithromycin, metronidazole, and levofloxacin. Methodology: A total of 82 patients with active H. pylori infection, confirmed by either a rapid urease test or a ¹³C urea breath test, were enrolled at our hospital. All participants received esomeprazole (40 mg) and amoxicillin (1,000 mg), 3 times daily for 14 days. Treatment success was assessed using a ¹³C urea breath test 4–6 weeks post-treatment. Safety was evaluated based on reported adverse effects. Results: Gastritis, gastric ulcer, and duodenal ulcer were present in 80.5%, 10.4%, and 9.1% of cases, respectively. The eradication rates according to intention-to-treat (ITT) and per-protocol (PP) analyses were 76.8% (63/82) and 81.8% (63/77), respectively. In the PP analysis, the eradication rate was 86.0% (49/57) in first-line treatment, and 70.0% (14/20) in patients with prior H. pylori treatment failure. Mild side effects, including nausea, abdominal discomfort, pruritus, diarrhea, and fatigue, were reported in 22.1% (17/77) of patients. Conclusions: This study demonstrates that a 14-day HDDT regimen provides relatively high efficacy and a favorable safety profile for first-line H. pylori eradication. Given the widespread resistance to clarithromycin, levofloxacin, and metronidazole in Vietnam; HDDT may serve as an alternative first-line therapy for H. pylori eradication in this region.